DESAIN KONTROL PID DENGAN METODA TUNING DIRECT SYNTHESIS UNTUK PENGATURAN KECEPATAN MOTOR DC - R.B.Moch. Gozali (Faculty of Industrial Technology Universitas Islam Indonesia, 2005)
PID controller is a controller which commonly used in industrial world. The importance of PID controller design is the ability to determine controller parameter or tuning. In this research, Direct Synthesis tuning method will be discussed.Generally, PLC is used as sequence regulator device. PLC also can be used as digital PID controller by using ASCII module (Omron) which has ability to adopt BASIC language programming. Direct Synthesis can be implemented by integrating PLC as PID controller with DC motor as a plant. Result shows that Direct Synthesis tuning method increase plant performance significantly. Keywords : PID controller, tuning, PLC